Vocational Competence-Oriented Curriculum Reform of PE Teaching in Higher Vocational Colleges - Hang, Chenggang (Journal of Theory and Practice of Contemporary Education, 2024)
With the development of the Times, all kinds of large companies put forward a higher demand for excellent employees. Higher vocational and technical colleges pay more attention to the integration of theory and practice, and pay attention to the training of talents'skills and vocational ability. Therefore, physical education guided by vocational skills in higher vocational colleges is helpful to improve students'employment competitiveness and promote their comprehensive quality.